2014
DOI: 10.4304/tpls.4.1.99-109
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Extrinsic vs. Intrinsic Motivation and Strategic Use of Language of Iranian Intermediate EFL Learners

Abstract: Abstract-This study aims to identify the learning orientations and language learning strategies of the students, to determine whether there are any significant differences in the motivational orientations and language learning strategies preferences between male and female learners, and investigate whether there is a relationship between students' motivational orientations and strategy preferences. A total of 206 intermediate level students who studied in English in private language institutes were asked to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
9
1
Order By: Relevance
“…Correlation between gender and LLS choice was measured. Females reported moderately higher levels of strategy use than males, in accordance with past, and ever-growing findings (Khazaie & Mesbah, 2014;Oxford, 1993;Oxford & Nyikos, 1989), indicating males lag behind females in the breadth of strategy use.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Correlation between gender and LLS choice was measured. Females reported moderately higher levels of strategy use than males, in accordance with past, and ever-growing findings (Khazaie & Mesbah, 2014;Oxford, 1993;Oxford & Nyikos, 1989), indicating males lag behind females in the breadth of strategy use.…”
Section: Resultssupporting
confidence: 83%
“…Instrumental motivation is a source of extrinsic motivation that refers to the practical pragmatic reason for language study and places a utilitarian value on learning for career advancement (Simmons, Dewitte, & Lens, 2000). Khazaie and Mesbah (2014) recognized that both intrinsic and extrinsic motivation influenced the frequency use and choice of reported LLS, with the highest correlation shared with affective strategies (r = .75 to .93, p < .01) and the lowest correlation shared with memory strategies (r = .23 to .54, p < .01). Moreover, results from a survey study by Shin and So (2018) revealed that higher levels of determination, mastery goal orientation, and internal regulation positively affected the use of cognitive, metacognitive, compensatory, and social strategies.…”
Section: Motivation and Language Learning Strategiesmentioning
confidence: 99%
“…Moghaddam et al (2019) indicated that the instructors most frequently used reflective techniques were metacognitive and cognitive components, and the least frequently used were practical components. Similarly, it was determined that female students employ cognitive, metacognitive, and social strategies more recurrently than male students (Khazaie & Mesbah, 2014;Oxford & Nyikos, 1989). There are also significant differences in their study between the males and the females in their use of memory, cognitive, and compensation strategies.…”
Section: Empirical Studies Related To Gender and Reflective Practicesmentioning
confidence: 99%
“…http://journal.uinjkt.ac.id/index.php/ijee | DOI: http://doi.org/10.15408/ijee.v7i2.17321 P-ISSN: 2356-1777, E-ISSN: 2443-0390 | This is an open access article under CC-BY-SA license Mesbah, 2014;Poornima et al, 2016). Teachers could influence learners' motivation through motivational strategies that refer to teachers' techniques to develop positive attitudes toward language learning (Dörnyei, 2001;.…”
Section: -200mentioning
confidence: 99%